2021
DOI: 10.1038/s41467-021-23003-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of poly(ADP-ribose) polymerase 9 (PARP9) as a noncanonical sensor for RNA virus in dendritic cells

Abstract: Innate immune cells are critical in protective immunity against viral infections, involved in sensing foreign viral nucleic acids. Here we report that the poly(ADP-ribose) polymerase 9 (PARP9), a member of PARP family, serves as a non-canonical sensor for RNA virus to initiate and amplify type I interferon (IFN) production. We find knockdown or deletion of PARP9 in human or mouse dendritic cells and macrophages inhibits type I IFN production in response to double strand RNA stimulation or RNA virus infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 67 publications
3
81
1
Order By: Relevance
“…Other reports also connect PARP9 to IFN signaling. PARP9 was recently discovered to be a non-canonical sensor for RNA viruses to promote type I IFN production via the phosphoinositide 3-kinase (PI3K)/AKT3 pathway ( Figure 4E ) [ 71 ]. Knockdown or deletion of PARP9 in dendritic cells, macrophages, or mice inhibits type I IFN production in response to double strand RNA (dsRNA) stimulation or RNA virus infection, including retrovirus, VSV, and IAV.…”
Section: The Roles Of Parps In Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reports also connect PARP9 to IFN signaling. PARP9 was recently discovered to be a non-canonical sensor for RNA viruses to promote type I IFN production via the phosphoinositide 3-kinase (PI3K)/AKT3 pathway ( Figure 4E ) [ 71 ]. Knockdown or deletion of PARP9 in dendritic cells, macrophages, or mice inhibits type I IFN production in response to double strand RNA (dsRNA) stimulation or RNA virus infection, including retrovirus, VSV, and IAV.…”
Section: The Roles Of Parps In Viral Infectionmentioning
confidence: 99%
“…Knockdown or deletion of PARP9 in dendritic cells, macrophages, or mice inhibits type I IFN production in response to double strand RNA (dsRNA) stimulation or RNA virus infection, including retrovirus, VSV, and IAV. Mechanistically, PARP9 uses its macrodomains for recognizing viral dsRNA, and interacts with PI3K p85 for activating downstream PI3K/AKT3 pathway, independent of mitochondrial antiviral-signaling (MAVS), limiting the RNA virus infection [ 71 ].…”
Section: The Roles Of Parps In Viral Infectionmentioning
confidence: 99%
“…PARPs are known ISGs and have shown to possess antiviral properties ( Zhu and Zheng, 2021 ). PAPR9 together with DTX3L promotes ISG expression during viral infection to enhance the immune response ( Zhang et al., 2015 ), and it has been suggested that PAPR9 serves as a non-canonical sensor for RNA virus to initiate and amplify type I IFN production in dendritic cells ( Xing et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the mitochondria, MAVS has also been found on peroxisomes, where it can induce a unique signaling pathway that specifically triggers IFNλ expression but not IFNβ in response to certain viral infections (Dixit et al, 2010;Odendall et al, 2014;Bender et al, 2015). Another sensor of RNA virus infection in Mϕ is poly ADPribose polymerase 9 (PARP9) (Xing et al, 2021). Interestingly, PARP9 is required to control RNA virus infection in STAT1dependent signal transduction, enhancing IFN-regulated host responses (Zhang et al, 2015).…”
Section: Viral Tricks To Avoid Pathogen Recognition Receptors Activationmentioning
confidence: 99%
“…Another sensor of RNA virus infection in Mφ is poly ADP-ribose polymerase 9 (PARP9) ( Xing et al, 2021 ). Interestingly, PARP9 is required to control RNA virus infection in STAT1-dependent signal transduction, enhancing IFN-regulated host responses ( Zhang et al, 2015 ).…”
Section: Viral Tricks To Avoid Pathogen Recognition Receptors Activationmentioning
confidence: 99%